Supporting the wellbeing of inner-city middle-school students through mindful and creative reflective activities. Issue 3 (4th May 2018) - Ahmed, Namarig; Schwind, Jasna K.
Abstract: Inner-city middle-school students encounter many intersections of the social determinants of health, while expected to learn and to excel academically. However, they lack skills to deal with stress, anger, frustration and sadness, often associated with their social context. To support student wellbeing, we developed a 7-week, 1-hour-session program, which took place during regular class time. Through use of creative reflective activities, namely, Schwind's Narrative Reflective Process and mindfulness, students learned skills that help support their social and academic wellbeing. Student feedback reveals that creative reflective activities and mindfulness helped foster their inter-intra personal skills in class, enhancing their learning experiences.